Phylogeography and population genetics of the riparian relict tree Pterocarya fraxinifolia (Juglandaceae) in the South Caucasus. Issue 1 (2nd January 2018) - Maharramova, Elmira; Huseynova, Irada; Kolbaia, Sandro; Gruenstaeudl, Michael; Borsch, Thomas; Muller, Ludo A. H.
Abstract : We aimed to (i) assess the extant genetic diversity of the riparian relict tree Pterocarya fraxinifolia across its current distribution range in the South Caucasus, including the past refugial areas Colchis and Hyrcan, and (ii) test if a separation of these areas is reflected in its phylogeographic history. Genetic diversity of natural populations was examined using nuclear microsatellite and plastid DNA markers. Spatial genetic structure was evaluated using Bayesian clustering methods and the reconstruction of plastid DNA networks. Divergence times of Colchic and Hyrcanian populations were estimated via divergence dating using a relaxed molecular clock. Allelic richness, private allelic richness, and expected heterozygosity were significantly higher in Hyrcan than in Colchis and the Greater Caucasus, and significant genetic differentiation was revealed between the two groups. Whereas only two plastid haplotypes were detected for the Colchic and Caucasian populations, the Hyrcanian populations displayed 11 different haplotypes. Significant isolation by distance was detected in Hyrcan. The most recent common ancestor of all P. fraxinifolia haplotypes was dated to a time well before a suggested glaciation period in the Caucasus during the late Pliocene (5.98 Ma [11.3–2.48 Ma HPD]). The widespread Colchic haplotype that also occurs along the southern slope of the Greater Caucasus and reaches south-eastern Azerbaijan has appeared more recently (0.24 Ma [1.41–0 Ma HPD]). This diversification pattern of Colchic haplotypes from ancient Hyrcanian haplotypes suggests a colonization of the region from south-east to north-west that predates the last glacial maximum (LGM). Natural populations of P. fraxinifolia show low-to-intermediate levels of genetic diversity and a significant decrease of diversity from Hyrcan to Colchis. However, the genetic differentiation between Colchic-Caucasian and Hyrcanian populations for nuclear markers suggests that independent gene pools existed in both areas at least since the LGM. Particular attention to conservation seems justified for the more diverse Hyrcanian populations.